TRINITY CHAPEL, CANTERBURY CATHEDRAL - Neal, David S.; Rodwell, Warwick ([S.l.] : OXBOW BOOKS, 2022)
Illustrated analysis of a unique mosaic pavement in Canterbury Cathedral, fragments of an original shrine and the surrounding royal tombs.
Foreword -- Preface -- Acknowledgements -- Summary Introduction -- 1. The Trinity and Corona chapels in context -- 2. The antiquarian record Part 1: The Mosaic and inlaid-roundel pavements -- 3. The Romanesque mosaic pavement in bay 1 -- 4. History and interpretation of the mosaic pavement -- 5. The pavement of figurative stone roundels in bay 1 -- 6. Interventions in the roundel pavement: 13th to 20th century Part 2: The Trinity chapel and shrines of St Thomas of Canterbury -- 7. Aspects of the archaeology of the Trinity and Corona chapels -- 8. The shrine pavement in bays 2 and 3 -- 9. St Thomas's shrine-tombs and their setting -- 10. The Corona chapel ('Becket's Crown') -- 11. Synthesis and discussion -- 12. The petrology of the tesserae and paving by Kevin Hayward -- 13. Appendices Notes to chapters -- Abbreviations -- Bibliography -- Index.
Includes bibliographical references and index.
In English.
eBooks on EBSCOhost
Keywords: Thomas, -- à Becket, Saint, -- 1118?-1170 -- Death and burial; Canterbury Cathedral -- History; Thomas, -- à Becket, Saint, -- 1118?-1170; Canterbury Cathedral; Mosaic floors -- England -- Canterbury; Religious architecture -- England -- Canterbury; Planchers en mosaïque -- Angleterre -- Canterbury; Architecture religieuse -- Angleterre -- Canterbury; Mosaic floors; Religious architecture; England -- Canterbury; Electronic books; History